EDUCATIONAL VIDEOS FOR ENGLISH BASIC VOCABULARY LEARNING IN THE SECOND GRADE OF BASIC EDUCATION IN THE EDUCATIONAL UNIT "LICEO ECOLÓGICO VIDA" ACADEMIC PERIOD 2016-2017. - VILLAPRADO ZAMBRANO, JIPSON FABIAN (2017)
IN PURSUIT OF HUMANITY´S LONGED-FOR DREAM OF HAVING A LINGUA FRANCA, THE ENGLISH LANGUAGE HAS TAKEN THE MOST APACE WORLDWIDE, AND HAS BECOME THE MAIN ELEMENT OF GLOBAL COMMUNICATION, BEING VERY IMPORTANT FOR THE CONDUCT OF INTERNATIONAL NEGOTIATIONS, IN ORDER TO BE ABLE TO ACCESS MORE INFORMATION, AND TO OBTAIN GREAT OPPORTUNITIES...